Saberes docentes na formação inicial de professores para a educação profissional técnica de nível médio - Silva, Fernanda Rebeca Araújo da (2016)
Understanding that Knowledge Teachers are important in the profession and are over the training process, we developed an investigative journey whose main objective was to understand in what ways the actions developed in undergraduate courses allow the construction of Knowledge Teachers for Vocational Education Level Technical medium (EPTNM). The locus of the research was the Federal Institute of Education, Science and Technology Amazon - Manaus Campus Center, and had as subjects the students of Degree courses in Biology, Chemistry, Physics and Mathematics of the institution. In view of the active participation of individuals, elected as a theoretical and methodological support action research, a process made possible the development of the discipline "Professional Education High School Technical", to degree courses. For us to reach this product initially seek to know the knowledge that proved necessary for teacher education to EPTNM along the historical trajectory of this education, with the epistemological positioning the design of Knowledge Teachers proposed by Tardif (2014), the same time contextualize this discussion establishing dialogues with Manfredi (2002), Kuenzer (2007), among others. Later in the meeting with the students, proceeded to listen to the experiences of the students of degrees in the EPTNM classrooms, and this took place in two main phases: 1) at the stage of diagnosis, with activities developed in Stage Seminar discipline and the meetings of the Fellowship Program Introduction to Teaching; 2) the development and implementation of a Short Course. The survey data, interpreted based on the Text Analysis and Discourse evidenced Knowledge Teachers for EPTNM: knowledge about this type of education and its characteristics; understanding of the integral formation of EPTNM of students in the social context in which they live; the construction of disciplinary joints within the curriculum, based on the work, science and technology. Resulting from the analysis of this knowledge, we understand that training activities should contemplate the epistemological, ontological and methodological aspects. The survey also shows as a result, the urgent need for discussions on the training processes for EPTNM the Federal Institutes such as identity element of their degree courses.